Prenatal Exposure to Maternal Cigarette Smoking and DNA Methylation: Epigenome-Wide Association in a Discovery Sample of Adolescents and Replication in an Independent Cohort at Birth through 17 Years of Age. - Lee, Ken W. K.; Richmond, Rebecca; Pingzhao Hu; French, Leon; Shin, Jean; Bourdon, Celine; Reischl, Eva; Waldenberger, Melanie; Zeilinger, Sonja; Gaunt, Tom; McArdle, Wendy; Ring, Susan; et al. (Environmental Health Perspectives, 2015)
Background: Prenatal exposure to maternal cigarette smoking (prenatal smoke exposure) had been associated with altered DNA methylation (DNAm) at birth. Objective: We examined whether such alterations are present from birth through adolescence. Methods: We used the Infinium HumanMethylation450K BeadChip to search across 473,395 CpGs for differential DNAm associated with prenatal smoke exposure during adolescence in a discovery cohort (n = 132) and at birth, during childhood, and during adolescence in a replication cohort (n = 447). Results: In the discovery cohort, we found five CpGs in MYO1G (top-ranking CpG: cg12803068, p = 3.3 × 10–11) and CNTNAP2 (cg25949550, p = 4.0 × 10–9) to be differentially methylated between exposed and nonexposed individuals during adolescence. The CpGs in MYO1G and CNTNAP2 were associated, respectively, with higher and lower DNAm in exposed versus nonexposed adolescents. The same CpGs were differentially methylated at birth, during childhood, and during adolescence in the replication cohort. In both cohorts and at all developmental time points, the differential DNAm was in the same direction and of a similar magnitude, and was not altered appreciably by adjustment for current smoking by the participants or their parents. In addition, four of the five EWAS (epigenome-wide association study)–significant CpGs in the adolescent discovery cohort were also among the top sites of differential methylation in a previous birth cohort, and differential methylation of CpGs in CYP1A1, AHRR, and GFI1 observed in that study was also evident in our discovery cohort. Conclusions: Our findings suggest that modifications of DNAm associated with prenatal maternal smoking may persist in exposed offspring for many years—at least until adolescence.